Conversor boost com indutor acoplado de arranjo diferencial com grampeador ativo com comutação em zero de tensão - Gonçalves, Tomás Adão (2022)
The population grouth and technological development led to increasing energy demand in the world, which leads many countries to look for fossil fuels to meet the increasing energy damand in the world. The use of fossil fuels, besides being limited, have being provoke ecosystem changes, endangering wildlife and animal in the earth planet. In this way, the looking for renewable sources has become an unovoidable challenge nowadays. The photovoltaic energy draw a big interest due to the numerous advantages it performs. However, photovoltaic panels in many applications can not meet the demand required for a system. High gain DC-DC converters are used to increase the panel voltage value to a bus value connected to the inverter required from the system. There are several techniques used to increase the voltage gain of DC-DC converters. Therefore, many of these techniques require the use of signicative numbers of components, which contributs to the cost, volume and complexity of the converter. This work approach about the coupled inductor technique applied to the boost converter. In coupled inductors, the energy stored in the leakage inductance when non-recycled, provoke a spike voltage on the switch which can permanently destroy it. The active clamp is used to clamp the voltage around the switch in a safe range of voltage operation and to regenerate this energy to the output. Furthermore, to prevant the dependence voltage gain on turn ratio, the differential arragement technique is applied, which make possible to achieve high voltage gains with turn ratio close to the unit. The complete study of the proposed converter is shown and the prototype experimental is presented. The result shows high output voltage of 240V, input voltage of 37.7V, with small duty cycle operating in a safe range of 0.448 and the turn ratio close to the unit. Both switches perform ZVS operation.The maximum efficiency achieved by the converter was 86%.